STUDENTS’ HIGHER ORDER THINKING SKILLS (HOTS) IN READING EXPOSITORY TEXT FOR SENIOR HIGH SCHOOL - Maria Rosari Oki; Mikhael Misa; Delti Yulita (English Study Program, Faculty of Teacher Training and Educational Sciences, Universitas Timor, 2025)
This study aims to analyze the high-order thinking skills (HOTS) of second-grade students at SMAN Noemuti in understanding expository texts. This study investigated students' abilities in evaluating, analyzing, making connections, drawing conclusions, and synthesizing information using HOTS-oriented assessments. This study used a quantitative method with a total of 25 students as samples. The results showed various levels of student competence: high, medium, and low. Evaluation and drawing conclusions were identified as the easiest skills, with synthesis as the most challenging. Students with high ability demonstrated critical thinking and creativity in applying HOTS, achieving excellent results in all categories. Students with medium ability demonstrated moderate proficiency, especially in connecting and summarizing ideas, while students with low ability experienced significant difficulties, especially in synthesizing information. Challenges faced by students included understanding complex vocabulary, handling application-based questions, and interpreting text structures. This study emphasizes the importance of tailored teaching strategies to improve HOTS, such as providing various levels of questions and engaging learning activities. This study offers insights for educators and future researchers to improve HOTS-based learning, fostering critical thinking and comprehensive reading skills that are essential for academic success.